The prospect [videorecording (DVD)] - Donnelly, Dana; Donnelly, Dana; Schultz, Robert (Comedian); Schultz, Robert (Comedian); Mahesh, Rishi; Prance (Actor) (X4 Pictures, 2026)
When high school senior Jerry Vanetti gets rejected from every college he applied to, he hatches a scheme to pose as an elite baseball prospect in order to trick a school into giving him an athletic scholarship...despite the fact that he's never played a sport in his life.